Anesthesiology Residency Training and the Anesthesia Toolbox: Five Years of Experience With a Collaboratively Developed Peer-Reviewed e-Learning System. Issue 2 (February 2021) - Woodworth, Glenn E.; Hoskins, Zachary B.; Hoang, Thomas T.; Marsh, Benjamin; Infosino, Andrew; Spofford, Christina M.; Maniker, Robert B.
Abstract : The Internet is a source of professional self-education for medical students and residents. Unfortunately, much of the content discovered through search engines is of insufficient quality for professional education. The Anesthesia Toolbox (AT) was developed to provide online peer-reviewed educational resources for anesthesiology trainees and faculty. Since 2014, AT has developed 24 curricula, 822 content items, and 3238 quiz questions. As of March 2020, 64 anesthesiology residency programs in the United States subscribed to the AT (41% of total). Since the onset of the pandemic in March, AT has added 25 programs (28% increase) and gained 1156 users (26% increase). Abstract : Supplemental Digital Content is available in the text.